Incidence and risk factors for late complications after the arterial switch operation. Issue 10 (5th July 2022) - Wang, Zhangwei; Li, Zhiqiang; Ding, Nan; Yi, Hanlu; Zhu, Yaobin; Yan, Daole; Li, Xiaofeng; Bai, Song
Abstract: Objective: The purpose of this study was to evaluate our institution's 16‐year arterial switch operation (ASO) experience and to determine early and late mortality and late morbidity, as well as the need for reoperation and catheter intervention, and finally, to explore risk factors for late complications and reintervention. Methods: The clinical data of 185 transposition of the great arteries (TGA) patients who received ASO treatment in our center from January 2006 to January 2022 were continuously included for retrospective study. Results: There were 13 early deaths (7.03%), 5 late deaths (3.01%), and 6 lost to follow‐up. The median follow‐up time for the 166 hospitalized survivors was 88.5 (2190) months. Moderate or above new aortic valve regurgitation (NAR; in this article, NAR represents moderate or greater reflux unless otherwise specified) occurred in 19 cases (11.45%), and aortic root dilation (ARD) occurred in 28 cases (16.87%). Late right ventricular outflow tract obstruction (RVOTO) occurred in 33 cases (19.88%). There were 18 patients (10.84%) who underwent late re‐intervention, and the most common indication for intervention was RVOTO, followed by recurrent aortic coarctation in patients undergoing concurrent arch repair and NAR or ARD. Receiver operating characteristics analysis found that NAR had the strongest predictive power for ARD, followed by RVOTO, followed by bicuspid native pulmonary valve (BPV), and aorto‐pulmonary diameter mismatch (APDMM) was the weakest. Multivariate analysis showed that APDMM, previous pulmonary artery banding (PAB), and mild NAR at discharge were independent risk factors for late NAR and ARD. Low surgical weight was an independent risk factor specific to NAR, and BPV was an independent risk factor specific to ARD. Older surgical age and ARD were independent risk factors for late RVOTO. Older surgical age, operation before 2014, late RVOTO, and late ARD were independent risk factors for late intervention. No reintervention events for coronary dysfunction were found in the late stage, but one patient occurred myocardial infarction due to coronary embolism after reoperation. Conclusion: Early and late survival rates after ASO in TGA patients have been remarkably improved in recent decades. Increased rates of NAR, ARD, recurrent coarctation of the aorta, and RVOTO as children age are major future outcomes of concern and may imply more late reinterventions. Careful follow‐up of neo‐aortic valve and root function is imperative, especially in patients with APDMM, previous PAB, mild NAR at discharge, low surgical weight, and BPV structures.